A novel NPHS1 variant in a Chinese infant with congenital nephrotic syndrome: a case report and literature review - Zhang, Wei; Hou, Li Min; Cheng, Xian (Frontiers in Pediatrics, 2025)
Congenital nephrotic syndrome is a rare autosomal recessive genetic disorder, with the Finnish type caused by NPHS1 variants being the most common. It is characterized by massive proteinuria, hypoalbuminemia, hypercholesterolemia, and edema, ultimately progressing to end-stage renal disease. To date, 260 genetic variants in NPHS1 have been reported, with two variants prevalent in Finnish patients, while non-Finnish populations exhibit greater genetic heterogeneity. This case report describes a Chinese Han female neonate with Finnish-type CNF, highlights the characteristics of her gene variants, and discusses the genetic heterogeneity of Finnish-type CNF between Asian and Finnish populations.